Razvoj uporabnih termografskih metod - Andrassy, Mladen (Strojniški vestnik, 2000)
Thermography is a contactless method for measurement of temperature and its distribution on the surfaces of objects. It is based upon the registration of infrared(IR) radiation from the object. Modern thermographic devices give the real-time surface temperature distribution, which combined with the absense of any contact is the basic advantage of the method. This makes thermography a very useful tool which has applications in all technical areas including medicine, biology etc. The following review provides the basics of termography and a couple of examples from qualitative and quantitative thermography indicating the wide spectrum of possible applications of this measuring technique in the field of surveillance, product development and scientific research.
Keywords: termografija; razvoj metod; naprave termografske; uporaba termografije; temperatura; merjenje